Using co-design to develop interventions to address health literacy needs in a hospitalised population - Rebecca L. Jessup; Richard H. Osborne; Rachelle Buchbinder; Alison Beauchamp (BMC, 2018)
Abstract Background Health literacy describes the cognitive and social skills which determine the motivation and ability of individuals to gain access to, understand and use information in ways which promote and maintain good health. Suboptimal health literacy is common and is believed to impact up to 60% of Australians. Co-design is a participatory approach to the development of interventions that brings together to staff and patients to design local solutions to local problems. The aim of this study is to describe a staff and patient co-design process that will lead to the development of health literacy interventions in response to identified health literacy needs of hospital patients. Methods A mixed methods, two-step sequential explanatory design. Step 1: hospitalised patients surveyed and data analysed using hierarchical cluster analysis to establish health literacy profiles. Step 2: clusters presented as vignettes to patients and clinicians to co-design interventions to address needs. Results Eight health literacy clusters were identified from surveys. Seven patients attended two patient workshops and 23 staff attended two staff workshops. Three key themes were identified: organisational, provider-patient, and patient self-care. Within these, five sub-themes emerged: "Good quality communication during hospital stay", "Social support for health", "A good discharge", "Care across the continuum" and "Accessing quality information when home". Fifteen potential interventions were produced, including changes to message design and delivery, staff training in assessing for understanding, social support to improve understanding, improving communication consistency across the care continuum, and strategic dissemination of web-based resources. Conclusion This study identified fifteen strategies to address health literacy needs of a hospital population. Implementation and evaluation will identify sets of strategies that have the maximum patient, clinician and organisational benefit. This approach allows for the development of locally-driven, contextually-appropriate interventions to address health literacy needs.